»Gute Psychotherapie« Verhaltenstherapie und Psychoanalyse im soziokulturellen Kontext - Lebiger-Vogel, Judith (Vandenhoeck & Ruprecht, 2011)
Psychotherapy as a profession, Freud said, was "impossible." Whoever decides to nevertheless take up psychotherapy is confronted by the question: Which method is seen today as the "best" method of psychotherapy? And why?Judith Lebiger-Vogel does not see the present boom of behavioural therapy and the retreat of psychoanalysis - as many other textbooks of psychology do - as representing "scientific progress"; rather, she sees it in the light of modern views of illness and treatment, the increasing emphasis on performance and success in life, and a fundamental shift in preferred therapy methods. What is presently considered "good" psychotherapy? How does this contribute to how students choose their later professions? These are the themes discussed in this volume from psychoanalytic, psychological and sociological perspectives
Keywords: Adoleszenz; Fachkultur; Gesellschaftskritik; Globalisierung; Hermeneutik; Historische Psychologie; Identität; Identitätsentwicklung; Konstruktivismus; Ökonomisierung; Positivismus; Postmoderne; Psychoanalyse; Psychologie; Psychotherapie; Psychotherapieforschung; Sozialisation; Sozialpsychologie; Soziologie; Studie; Typenforschung; Universität; Verhaltenstherapie; Wissenschaftstheorie